PD-1/PD-L1 and coronary heart disease: a mendelian randomization study - Zeng, Liangjia; Liang, Yinglan; Zhou, Ruoyun; Yang, Wenting; Chen, Kexin; He, Baixin; Qiu, Yuqing; Liu, Linglong; Zhou, Deyang; Xiao, Zhaolin; Liang, Haowen; Zhang, Binghua; et al. (Frontiers in Cardiovascular Medicine, 2024)
It has been found that programmed cell death protein-1 (PD-1) or its ligand PD-L1 may play an important role in the onset and progression of coronary heart disease (CHD). Thus, we conducted this mendelian randomization analysis (MR) to estimate the causal relationship between PD-1/PD-L1 and 5 specific CHDs (chronic ischemic heart disease, acute myocardial infarction, angina pectoris, coronary atherosclerosis, and unstable angina pectoris), complemented by gene set enrichment analysis (GSEA) for further validation. Publicly available summary-level data were attained from the UK Biobank with genetic instruments obtained from the largest available, nonoverlapping genome-wide association studies (GWAS). Our analysis involved various approaches including inverse variance-weighted meta-analysis, alternative techniques like weighted median, MR-Egger, MR-multipotency residuals and outliers detection (PRESSO), along with multiple sensitivity assessments such as MR-Egger intercept test, Cochran's Q test, and leave-one-out sensitivity analysis to evaluate and exclude any anomalies. Gene expression profile (GSE71226) was obtained from Gene Expression Omnibus (GEO) database for GSEA. IVW analysis showed a causal association between PD-1 and chronic ischemic heart disease (OR, 0.997; 95%CI, 0.995 -0.999; P, 0.009), chronic ischemic heart disease and PD-1 (beta, -3.1; 95%CI, -6.017–0.183; P, 0.037), chronic ischemic heart disease and PD-L1 (beta, -3.269; 95%CI, -6.197 –0.341; P, 0.029). No significant causal relationship was found between PD-1/PD-L1 and other 4 CHDs. The accuracy and robustness of these findings were confirmed by sensitivity tests. GSEA found that the KEGG pathway and related core genes of "PD-L1 expression and PD-1 checkpoint pathway in cancer" pathway were downregulated in CHD. This study provided evidence of a bidirectional causal relationship between PD-1 and chronic ischemic heart disease and a protective association between chronic ischemic heart disease and PD-L1.